Development of a valid and reliable instrument to evaluate competence on nasogastric tube feeding - Dagundon, Joselito R., Jr.; De Guzman, Lianmuel R.; De Juras, Rudolph John R.; Dela Cruz, Jhonry C.; Dungca, Ralph Deniel T.; Elvambuena, Bryan F.; Esta, Khirstie Ruth S.; Galban, Dexter A.; Gallegos, Cleoanne Lourdes P.; Garcia, Jao Jarro B. (Manila College of Nursing University of the Philippines Manila, 2013)
In the UP College of Nursing, the competency for nasogastric tube feeding is taught and evaluated using a skills checklist. This checklist, however, has not yet been tested for validity and reliability. This study aims to develop a valid and reliable checklist to evaluate competence on the said skill. Utilizing a descriptive exploratory design, five experts on NGT feeding validated a refined skills checklist. Steps with a computed CVI of ≤ 0.6 were removed, Five inter-raters then evaluated two sets of three student- nurses to test for reliability. First round free-marginal multi-rater kappa scores were 0.793, 0.770, and 0.816 while second round scores were 0.847, 0.880, and 0.882. Appropriate modifications were then made. The results showed that the checklist developed is valid and reliable enough to be utilized as a teaching and evaluation tool by different colleges of nursing.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, April 2013.
Keywords: Nursing -- Research